Tinjauan Literatur Kualitatif tentang Dampak Paparan Bahan Kimia terhadap Kesehatan Pekerja Industri - Tamin, Tiara Putri Azzahra; Putri, Abellia; Purba, Tiara Khairani Br; Hasibuan, Abdurrozzaq (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Chemical exposure in industrial environments is a major risk factor contributing to adverse health outcomes among workers. This study aims to analyze the impact of chemical exposure on industrial workers’ health through a qualitative literature review by examining scientific articles published between 2020 and 2025 from electronic databases such as Google Scholar and ResearchGate  ￼. The findings indicate that exposure to chemicals such as benzene, mercury, organic solvents, and toxic gases exerts significant toxic effects on multiple physiological systems, including the respiratory, nervous, and reproductive systems, as well as vital organs such as the liver and kidneys, with primary exposure routes through inhalation, dermal contact, and ingestion. Most studies report exposure levels within moderate to high-risk categories, with the potential to cause both acute and chronic health effects, including degenerative diseases and malignancies. Determinant factors influencing risk levels include duration of exposure, compliance with personal protective equipment (PPE) usage, workplace ventilation conditions, and workers’ knowledge levels. Therefore, comprehensive risk control measures are required through the implementation of the hierarchy of controls, strengthening occupational health and safety (OHS) management systems, and enhancing worker education and training to establish a safe, healthy, and sustainable working environment.